Exploring beliefs about dietary supplement use: focus group discussions with Dutch adults. Issue 15 (3rd August 2017) - Pajor, Emília Margit; Oenema, Anke; Eggers, Sander Matthijs; de Vries, Hein
Abstract: Objective: Although dietary supplement use is increasing in Europe and the USA, little research involving adults' beliefs regarding dietary supplements has been conducted. Therefore, the present study aimed to explore and compare users' and non-users' beliefs towards dietary supplements. Design: Thirteen focus group discussions were conducted of which seven groups were dietary supplement users and six groups were non-users. Based on the socio-cognitive factors of the Integrated Change Model, a semi-structured topic guide was set up. The discussions were audio-recorded and subjected to qualitative content analysis, applying the framework approach. Setting: Data were collected in Maastricht, the Netherlands, in 2014 and 2015. Subjects: In total fifty-six individuals participated in the study, of whom twenty-eight were dietary supplement users and twenty-eight non-users. The average age of participants was 42·9 years. Results: Dietary supplement users' attitude beliefs were mainly related to mental and physical health enhancement, illness prevention and curative health benefits. Users were critical of the nutritional knowledge of health professionals and of the quality of food products. Non-users were convinced that the human body does not need any support and that regular food is enough to cover one's nutritional needs. Users and non-users held comparable beliefs regarding the definition and risks of dietary supplements, and perceived social influences. Conclusions: In their decision about dietary supplement use, both groups were guided by their own convictions to a great extent. Both groups would benefit from improved understanding of the health effects of dietary supplements to improve informed decision making.